Media reporting of suicide and adherence to media guidelines. (September 2018) - McTernan, Niall; Spillane, Ailbhe; Cully, Grace; Cusack, Eimear; O'Reilly, Theresa; Arensman, Ella
Background: International research consistently shows evidence for an association between sensationalised and detailed media reporting, and suicidal behaviour. Aim: This study examined the quality of media reporting of suicide and adherence to media guidelines in Ireland. Methods: In accordance with the criteria outlined in the media guidelines for reporting suicide, 243 media articles were screened and analysed for quality of reporting of two high-profile cases of suicide and two cases of suicide that became high profile following a period of intense media coverage that occurred between September 2009 and December 2012. Results: A minority of articles breached the media guidelines in relation to sensationalised language (11.8%), placement of reports on the front page of the newspaper (9.5%), publishing of inappropriate photographs (4.2%) and mention of location of suicide (2.4%), while no articles disclosed the contents of a suicide note. However, in the majority of articles analysed, journalists did not refer to appropriate support services for people vulnerable to, and at risk of suicide (75.8%) or mention wider issues that are related to suicidal behaviour (53.8%). Overemphasis of community grief (48.3%) was also common. Nearly all articles (99.2%) breached at least one guideline and 58.9% of articles breached three or more guidelines. Conclusion: Overall, adherence to media guidelines on reporting suicide in Ireland improved in certain key areas from September 2009 until December 2012. Nonetheless, important challenges remain. Increased monitoring by media monitoring agencies, regulators and government departments is required. Implementation should be conducted using a pro-active approach and form part of the curriculum of journalists and editors. The inclusion of guidelines for the reporting of suicidal behaviour in press codes of conduct for journalists warrants consideration.